2010
DOI: 10.1111/j.1447-0349.2010.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Attributional style of Egyptians with schizophrenia

Abstract: The attributional style is one domain of social cognition that involves perceiving, interpreting, and generating responses to others' intentions and behaviours in different situations. This study describes the attributional style of Egyptians with schizophrenia. The study took place in a psychiatric hospital in Egypt. Eight psychiatric wards were randomly selected, and all participants (150) with a diagnosis of schizophrenia participated. Data were collected using the Ambiguous Intention Hostility Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Evaluators assessed hostility and aggression through answers that were subjectively drawn up by the participants. Combs et al [35] showed that the three items that measured blame had a Cronbach's alpha internal consistency of 0.83-0.86, and Elnakeeb et al [36] recorded a Cronbach's α of 0.81-0.83. In a study of the Korean version of the scale, which was conducted by Chang et al [34], Cronbach's alpha of internal consistency was 0.53, 0.61, and 0.75 for the three subscales, whereas, in this study, it was 0.72, 0.77, and 0.78, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluators assessed hostility and aggression through answers that were subjectively drawn up by the participants. Combs et al [35] showed that the three items that measured blame had a Cronbach's alpha internal consistency of 0.83-0.86, and Elnakeeb et al [36] recorded a Cronbach's α of 0.81-0.83. In a study of the Korean version of the scale, which was conducted by Chang et al [34], Cronbach's alpha of internal consistency was 0.53, 0.61, and 0.75 for the three subscales, whereas, in this study, it was 0.72, 0.77, and 0.78, respectively.…”
Section: Methodsmentioning
confidence: 99%